2005
DOI: 10.1111/j.1540-8167.2005.50054.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cryoenergy in the Ablation of Atrioventricular Reentrant Tachycardia Substrates in Children and Adolescents

Abstract: Cryoablation of SVT substrates in pediatric patients was associated with a lower success rate compared to RF catheter ablation. Cryomapping decreased the number of permanent lesions but did not predict cryoablation outcome in all tachycardia substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 26 publications
(68 reference statements)
3
87
1
8
Order By: Relevance
“…5 Overall, cryoenergy might offer a less aggressive and more titrated way to alter tissue with a better safety profile than RFCA and a comparable success rate. [7][8][9] The use of 6-mm-tip cryoablation catheters seems to enhance short-term success rates. 10,11 The present study was designed as a multicenter prospective randomized trial to test the hypothesis that cryoablation for AVNRT is as effective (both short term and long term) as RFCA with a lower risk of permanent AV block.…”
Section: Clinical Perspective On P 2245mentioning
confidence: 99%
“…5 Overall, cryoenergy might offer a less aggressive and more titrated way to alter tissue with a better safety profile than RFCA and a comparable success rate. [7][8][9] The use of 6-mm-tip cryoablation catheters seems to enhance short-term success rates. 10,11 The present study was designed as a multicenter prospective randomized trial to test the hypothesis that cryoablation for AVNRT is as effective (both short term and long term) as RFCA with a lower risk of permanent AV block.…”
Section: Clinical Perspective On P 2245mentioning
confidence: 99%
“…3 In children and adolescents, data from the pediatric radiofrequency catheter ablation registry acquired more than a decade ago reported a significant number of recurrences with 71% freedom from AVNRT 3 years post ablation. 4 However, recent follow-up studies of pediatric patients after AVNRT ablation reported freedom from AVNRT between 84% and 100% with radiofrequency 2,5 and between 78% and 93% with cryoenergy, [6][7][8] respectively. These studies on a limited number of pediatric patients analyzed data on the follow-up of 1 to 3 years post ablation.…”
mentioning
confidence: 99%
“…Literature reports acute success of AVNRT cryoablation in children ranging from 75% to 100% with a recurrence rate up to 27% 8, [26][27][28][29][30][31] . In our population acute success rate was 100% without complications.…”
Section: Discussionmentioning
confidence: 99%